Heterogeneous Costs of Alcohol and Drug Problems Across Cities and Counties in California. (16th February 2017) - Miller, Ted R.; Nygaard, Peter; Gaidus, Andrew; Grube, Joel W.; Ponicki, William R.; Lawrence, Bruce A.; Gruenewald, Paul J.
Abstract : Background: Estimates of economic and social costs related to alcohol and other drug (AOD) use and abuse are usually made at state and national levels. Ecological analyses demonstrate, however, that substantial variations exist in the incidence and prevalence of AOD use and problems including impaired driving, violence, and chronic disease between smaller geopolitical units like counties and cities. This study examines the ranges of these costs across counties and cities in California. Methods: We used estimates of the incidence and prevalence of AOD use, abuse, and related problems to calculate costs in 2010 dollars for all 58 counties and an ecological sample of 50 cities with populations between 50, 000 and 500, 000 persons in California. The estimates were built from archival and public‐use survey data collected at state, county, and city levels over the years from 2009 to 2010. Results: Costs related to alcohol use and related problems exceeded those related to illegal drugs across all counties and most cities in the study. Substantial heterogeneities in costs were observed between cities within counties. Conclusions: AOD costs are heterogeneously distributed across counties and cities, reflecting the degree to which different populations are engaged in use and abuse across the state. These findings provide a strong argument for the distribution of treatment and prevention resources proportional to need. Abstract : Per capita, alcohol abuse cost 3, 450 and drug abuse cost 1, 175 in California in 2010. The burden was concentrated in the more rural northern and central areas of the state excluding the San Francisco Bay area. Alcohol burden always exceeded drug burden. The difference was greatest in the north central valley, more rural southern counties and Los Angeles. Illicit drug use played a more prominent role in the state's northern tier and San Francisco Bay area.